Optimizing STEM Education via e-Learning: Addressing Challenges and Strategic Planning for Graduate Employment Outcomes - Al Shamsi, Ibrahim Rashid (Emerging Science Journal, 2024)
This study fills a significant vacuum in the literature and offers insightful information, especially pertinent to the Arabic and Gulf areas. In support of the socioeconomic development and diversification initiatives in these areas, it encourages the creation of educational policies and practices that can improve student job chances. Educators and policymakers play a crucial role in implementing these recommendations, ensuring that effective STEM education equips future generations with the knowledge and skills to navigate and secure digital environments, mitigating risks posed by cyber threats. By preparing students to excel in STEM disciplines, they ensure that the future workforce is ready to contribute to and shape a safer, more innovative future. Today's STEM workforce requires continuous education to stay abreast of advancements in STEM fields. Online delivery of STEM courses enables higher education institutions to collaborate effectively with industry partners, minimizing disruptions to productivity. This study aims to evaluate the enhancement of students' STEM knowledge and skills through e-learning platforms using Structural Equation Modeling (SEM). The dataset comprises 212 participants and 15 indicators, analyzed using measurement and structural models. Results indicate significant findings supporting hypotheses: E-Learning (E.L.) improving Student employment opportunities (SEO) (B=0.539, t=8.884, p=0.000) and E.L. improving STEM (B=0.465, t=8.849, p=0.000), validating H1 and H2, respectively. H3 explores how possessing STEM knowledge mediates E-Learning's impact on SEO, revealing a notable indirect relationship (B=0.082, t=2.303, p=0.021). Integrating E-Learning with STEM fosters a robust digital infrastructure, addressing talent shortages and improving human resource management amidst global technological advances. Online STEM courses are increasingly recognized as a viable solution to national STEM challenges, overcoming traditional adoption barriers. Doi: 10.28991/ESJ-2024-SIED1-014 Full Text: PDF